(3bGYOI aj GdGSe hGdeSeis - (3CMeO Hf YHO GdMdje Hf YHO GdSdGe GdMQGfj, Jbj GdOjf, GHf JjejI, CHh GdYHGS , J (B728 (3g` s
(3ChdgG (B:s
(3GdMeO ddg fSJYjfg hfSJZaQg hJYhP HGddg ef TQhQ CfaSfG hef SjFGJ CYeGdfG aUd ai GdGSe hGdeSei gd gh gh Ch ZjQg ChdG jbGd ghgh hdG jbGd gh ZjQg s
(3BNQgG (B:s
(3hLQi GdcdGe ai Pdc abdfG jYWi HMSH GdeUdMI aWdH GdeOQS GdNeS HfGA Ydi gPG GdXf abjd dg aCYWi Gdbje CjVkG GdNeS dCfg fXjQ GdeOQS aXgQ HWdGf MLJg BNQg hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B144 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B261s
Keywords: (3GdfMhs